Enabling Practical Decision Making For Sustainable Green Data Center Planning - Muhamad Faris Naufal Austen; Athor Subroto (Jurnal Ekonomi, 2023)
Data centers play a crucial role in storing and processing data in today's digital age, leading to a surge in demand for sustainable green data center planning. However, implementing practical measures to achieve sustainability remains a challenge for data center managers. This study aims to aid their informed decision-making in sustainable green data center planning. Previous research has identified seven green data center key components: ICT governance, infrastructure, energy, equipment lifecycle, green technology, benchmarking, and business continuity. Subsequently, the study expanded by utilizing the FAHP method to evaluate the perspectives of various experienced data center. Those green data center components were evaluated against each other regarding the three sustainability criteria: environment, economy, and corporate. Consequently, it was discovered that infrastructure, green technology, and business continuity consistently held the highest fuzzy weight in multiple sensitivity analysis scenarios. Thus, data center managers can allocate resources based on priority rankings and adjust accordingly.